So «where to go», psychiatry, or antipsychiatry hidden - G. N. Nosachev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The article is an institutional discourse with article N.G. Neznanov with the co-authors of «Where go?». From the standpoint of the philosophy of science discusses some of the signs of the crisis of modern psychiatry in the period of postmodernism, in an illustration taken any attempt to replace the addiction to addictology and expansion of domestic neurologists in the diagnosis and therapy of the syndrome of dementia. An attempt is made on the basis of the methodology and philosophy of science, the principle of demarcation to show the way out of the crisis and out of crisis in psychiatry.